Assessment of metal concentrations in tap-water – from source to the tap: a case study from Szczecin, Poland - Górski, Józef; Siepak, Marcin (Wydawnictwo Naukowe UAM, 2014)
The concentrations of Al, As, Cd, Cu, Pb, Zn, Ni, Fe and Mn were determined in June 2010 for 100 tap-water samples, collected directly at consumers in the older part of the city of Szczecin (Poland). Increased concentrations of metals were thus detected. This concerns mainly Fe (19% of samples showed concentrations above drinking-water quality standards) and Pb (5%). In some samples, the maximum admissible concentration levels for Mn, Cu and Ni were also exceeded. This was not the case for Al, despite the use of aluminium compounds during water treatment; the Al con -centrations in treated water were, however, significantly higher than in raw water. It was also found that (1) the corrosive properties of water (low alkalinity and increased concentration of sulphates), (2) the water-treatment processes causing a decrease of the pH and an increase of the CO 2 , and (3) transport of the treated water over long distances (30 km) provide favourable conditions for the leaching of metals from water-pipe networks. The type of material used in domestic plumbing and the content of Ce, Fe, Mn, Ni and Cd in the tap-water at consumers show a correlation. The high content of Pb is mainly a result of lead pipes connecting the network to the buildings.
Keywords: chemical quality; water-distribution networks; metals; tap–water